2012
DOI: 10.1021/nn304541h
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanoparticles to Control the Differentiation of Neural Stem Cells in the Subventricular Zone of the Brain

Abstract: Herein, we report the use of retinoic acid-loaded polymeric nanoparticles as a potent tool to induce the neuronal differentiation of subventricular zone neural stem cells. The intracellular delivery of retinoic acid by the nanoparticles activated nuclear retinoic acid receptors, decreased stemness, and increased proneurogenic gene expression. Importantly, this work reports for the first time a nanoparticle formulation able to modulate in vivo the subventricular zone neurogenic niche. The work further compares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 53 publications
1
80
0
Order By: Relevance
“…microRNAs) [6][7][8][9] regulate the neurogenic niche. MicroRNAs (miR) are able to regulate hundreds of genes [10] at the posttranscriptional level by inhibiting mRNA translation or inducing mRNA degradation [11].…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs) [6][7][8][9] regulate the neurogenic niche. MicroRNAs (miR) are able to regulate hundreds of genes [10] at the posttranscriptional level by inhibiting mRNA translation or inducing mRNA degradation [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, proliferating astrocytes (GFAP+/Ki67+) decreased in a similar fashion when treated with either 60 sec of laser or the combination of LR-NP+60s. We have previously reported that RA-loaded polymeric nanoparticles do not affect NSC astrocytic differentiation [39], as such, this new result might indicate that decreased astrocytic proliferation is a characteristic restricted to laser-induced differentiation.…”
Section: Discussionmentioning
confidence: 53%
“…Importantly, functionalized nanostructured hydrogels were shown to successfully induce NSC differentiation while supporting tissue regeneration [6]. Recently, we have successfully developed a NP formulation capable of controlling NSC differentiation both in vitro and in vivo [3,4]. Contrary to soluble retinoic acid (RA), our results demonstrated that RA-NPs injected intracerebroventricularly contributed to the successful neuronal commitment of mouse subventricular zone (SVZ) NSCs.…”
Section: Modulation Of Endogenous Nscsmentioning
confidence: 85%
“…Nanoparticulate systems for brain delivery (e.g., anticancer drugs, analgesics, antiAlzheimer's and anti-Parkinson's drugs) have been described in the past 25 years [2]. However, modulation of the activity/ differentiation of NSCs by nanoparticulate systems releasing small molecules was only recently demonstrated [3,4]. Current progress in the nanomedicine field has been stimulated by better understanding the biology of NSCs and by identifying molecular players capable of modulating their activity, proliferation, migration, and differentiation.…”
Section: From Neural Stem Cells To Nanomedicinementioning
confidence: 99%